Front Cover: Catalyst–Electrolyte Interactions in Aqueous Reline Solutions for Highly Selective Electrochemical CO2 Reduction (ChemSusChem 2/2020). Issue 2 (20th January 2020) - Garg, Sahil; Li, Mengran; Rufford, Thomas E.; Ge, Lei; Rudolph, Victor; Knibbe, Ruth; Konarova, Muxina; Wang, Geoff G. X.
Abstract : The Front Cover shows the electrochemical conversion of CO2 to CO over a silver foil electrode in reline solution, which is a deep eutectic solvent of choline chloride and urea. In reline the silver foil was roughened by (i) dissolution of oxide layers followed by (ii) electrodeposition of Ag nanoparticles on the cathode. This surface restructuring exposes low‐coordinated Ag atoms, and the subsequent adsorption of choline ions and urea at the catalyst surface limits proton availability in the double layer and stabilizes key CO2 reduction intermediates such as *COOH. These approaches could potentially be extended to other electrocatalytic metals and applications. More information can be found in the Full Paper by S. Garg et al. on page 304 in Issue 2, 2020 (DOI: 10.1002/cssc.201902433 ).